Cost differentials of dental outpatient care across clinical dentistry branches - Rančić, Jovana; Rančić, Nemanja; Majstorović, Nemanja; Biočanin, Vladimir; Milosavljević, Marko; Jakovljević, Mihajlo (Farmeconomia. Health economics and therapeutic pathways, 2015)
Background: Dental care presents affordability issues in Central & Eastern European transitional economies due to lack of insurance coverage in most countries of the region and almost complete out-of-pocket payments by citizens. Objective: Real world estimates on cost differentials across clinical dentistry branches, ICD-10 diagnostic groups and groups of dental services. Methods: Prospective case-series cost analysis was conducted from the patient perspective. A six months time horizon was adopted. Sample size was 752 complete episodes of treatment in 250 patients, selected in 2012/2013 throughout several specialist state- and private-owned dental clinics in Serbia. All direct costs of dental care were taken into account and expressed in Euros (€). Results: Mean total costs of dental care were € 46 ± 156 per single dentist visit while total costs incurred by this population sample were € 34,424. Highest unit utilization of services belongs to conservative dentistry (31.9%), oral surgery (19.5%) and radiology (17.4%), while the resource with the highest monetary value belongs to implantology € 828 ± 392, orthodontics € 706 ± 667 and prosthetics € 555 ± 244. The most frequently treated diagnosis was tooth decay (33.8% unit services provided), pulpitis (11.2%) and impacted teeth (8.5%), while most expensive to treat were anomalies of tooth position (€ 648 ± 667), abnormalities of size and form of teeth (€ 508 ± 705) and loss of teeth due to accident, extraction or local periodontal disease (€ 336 ± 339). Conclusion: Although the range of dental costs currently falls behind EU average, Serbia’s emerging economy is likely to expand in the long run while market demand for dental services will grow. Due to threatened financial sustainability of current health insurance patterns in Western Balkans, getting acquainted with true size and structure of dental care costs could essentially support informed decision making in future.